Nível de flexibilidade obtido pelo teste de sentar e alcançar a partir de estudo realizado na grande São Paulo - Ribeiro, Cibele Calvi Anic [UNIFESP] (2010)
Objective: Examine the level of flexibility of men and women in different ages through the sit and reach test protocol and classify them in accordance with the Canadian Standardized Test of Fitness (CSTF), and from results, draw up a new table that reflects the population analyzed. Methods:16405 individuals physically active and sedentaries were divided in different age groups: 15 to 19 (n = 954), 20 to 29 (n = 2916), 30 to 39 (n = 2161), 40 to 49 (n = 2333), 50 to 59 (n = 2739), 60 to 69 (n = 3195), above 70 (n = 2107). For preparation of the table, the percentiles were calculated for the scores of the test. The percentiles 20, 40, 60 and 80 mentioned above were used as cutoff to generate the ratings: poor, below average, average, above average and excellent, respectively. Results: According to table proposed by CSTF the age groups from 15 to 39 were classified as poor with a flexibility average ranging from 24,805±9,684cm and 26,130± 10,111cm in females and between 21,480±9,905cm and 22.848±9,648cm in males. In the categories from 40 to 69 the average flexibility ranged between 22,768± 9,627cm and 25,396±9,547 in females and between 16,396 ±10,136cm and 19,935±9,192cm in males were classified as below average. Conclusions: Although most of the samples were practicing regular exercise, the average flexibility level presented did not correspond to the average suggested by the CSTF demonstrating the importance of building national reference tables and to establish new normative values as the scale proposed by this work.